Impact of multiple reflow on intermetallic compound of nickel-doped tin-silver-copper on ENImAg substrate - M.A., Rabiatul Adawiyah; S.A., Amirul; O., Saliza Azlina; H., Syafiq (Wiley-VCH Verlag, 2020)
The growth of intermetallic compounds (IMCs) of the tin-silver-copper-nickel/electroless nickel immersion silver (SACN/ENImAg) at the 230 °C during multiple reflows was investigated. The characterization analysis of the samples was conducted using scanning electron microscopy and assisted by a dispersive x-ray analysis. A layer of continuous (Cu, Ni)6Sn5 and discontinuous (Ni, Cu)3Sn4 intermetallic were formed at the interface after up to the third reflow, while Ag3Sn nanosized was formed on the intermetallic surface. The total thickness of the intermetallic layer increased as the reflow increased. The findings also revealed that the intermetallic thickness became thicker with the mass percentage of nickel increased. Hence, the intermetallic growth was controlled mainly by reflow times and nickel content in solders.